A critical discourse analysis of China’s national image construction: insights from the Swahili news corpus - Qin, Zulong (Journal of China Computer-Assisted Language Learning, 2025)
With the increasing frequency of China–Africa interactions, the importance of Swahili in China–Africa relations is steadily growing. However, there is still a notable lack of research on Swahili news corpora and discourse analysis. This study adopts both quantitative and qualitative methods to examine China’s national image construction through media under the critical discourse analysis (CDA) framework. Focusing on the mainstream media China Radio International (CRI), a micro corpus was built to analyse word frequency, word clusters and concordance lines, with the aim of exploring linguistic features and discourse structures of news reports. The findings indicate that by covering China’s efforts in promoting China–Africa affairs with positive discourse, CRI generally holds a positive attitude in news reports to construct a responsible global actor role. Meanwhile, CRI’s discourse construction also exhibits an imbalance in lexical choice with a tendency to emphasize positive achievements while downplaying challenges and difficulties. This reflects underlying power dynamics, socio-cultural influences, and ideological tendencies. This study could provide a reference for optimizing the construction of China’s image in Africa through African indigenous language media.